Strategi Profesional Guru Bersertifikasi dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran PAI di SDN 010 Bangko Pusako - Fadilah Julya Putri; Qonita Az Zahra; Nur Azizah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of digital technology has provided students with easier access to religious information through the internet and social media. However, this condition also presents challenges because not all circulating information reflects the values of religious moderation. This study aims to analyze the role of Islamic Religious Education (PAI) teachers in developing students’ understanding of religious moderation in the digital era. The research employed a descriptive qualitative approach conducted at SDN 010 Bangko Pusako, Rokan Hilir Regency. The research subjects consisted of PAI teachers as the main informants, while the principal and students served as supporting informants. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model involving data reduction, data presentation, and conclusion drawing. The findings indicate that PAI teachers understand religious moderation as a balanced, tolerant attitude that respects differences. Teachers play significant roles as educators, mentors, and role models in instilling moderation values through discussion methods, contextual examples, and the use of digital media. The main challenge faced is the abundance of unverified religious information on social media that may influence students’ understanding. This study implies that PAI teachers have a strategic role in shaping moderate religious attitudes through interactive learning and continuous guidance in the digital era.